Regulation issues in the banking industry - Pereira, João André Calviño Marques (2011)
This dissertation aims to examine the factors that drive the bank decision process of capital/investment structure and to evaluate the effectiveness of regulatory intervention in Brazil. This study is divided into three chapters. The first chapter presents, in a systematic fashion, the theoretical and empirical literature to explain the financing and investment decisions of a heavily regulated banking firm. It also describes the evolution of international standards of prudential capital regulation, since the publication of the first Basel Accord until the initial steps of Basel III, and the regulatory scenario in Brazil. The second chapter, through a dynamic model of the trade-off theory, analyzes the determinants of Brazilian banks‟ capital buffer between 2001 and 2009, suggesting that: (i) regulatory capital requirements and adjustment costs may influence banks decisions; (ii) supervisory authority evaluations may impact capital buffers; (iii) market discipline may not being effective in improving bank solvency; and (iv) there is a negative relationship between the buffer and business cycle, which may represent a pro-cyclical bank’s capital management. Finally, the third chapter uses supervisory authority ratings (CAMEL) to provide evidences that the supervisory and regulatory pressures induce banks in Brazil to undertake downwards short term adjustments in leverage and also in portfolio risks.